2016
DOI: 10.1002/anie.201607237
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Carbon–Carbon Bond Breaking and Spin Equilibria in Bis(pyrimidinenorcorrole)

Abstract: Reversible homolytic dissociation of the bis(pyrimidinenorcorrole) σ-dimer was elucidated by means of variable temperature ESR and H NMR spectroscopy, mass spectrometry, and optical spectrocopy. Dehydrogenation of the σ-dimer yielded another dimer displaying a singlet-triplet equilibrium in solution, strong NIR absorption (1570 nm), and a narrow electrochemical HOMO-LUMO gap (0.74 V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 77 publications
1
43
0
2
Order By: Relevance
“…[2f] Recently Wu andc o-workersr eported that, in the case of benzannulatedTs chitschibabin hydrocarbon 3,t he closed-shell quinonoid state 3-CS was destabilizedb yi ntramolecular steric repulsion between the two anthracene units (Scheme 1). [4] Then it occurred to us that the similarc ontrolo fo pen-shell structure mightb ep ossible for 2 by replacing the central metals.G enerally,N i II -porphyrins tend to take non-planar structuress uch as ruffled and saddle-like conformationso wing to the relatively short NÀNi II distances, whereasZ n II -porphyrins prefer planars tructures. In addition,Li, Chmielewski, and co-workers also observed as imilare quilibrium in a pyrimidinenorcorrole dimer.…”
Section: Introductionmentioning
confidence: 99%
“…[2f] Recently Wu andc o-workersr eported that, in the case of benzannulatedTs chitschibabin hydrocarbon 3,t he closed-shell quinonoid state 3-CS was destabilizedb yi ntramolecular steric repulsion between the two anthracene units (Scheme 1). [4] Then it occurred to us that the similarc ontrolo fo pen-shell structure mightb ep ossible for 2 by replacing the central metals.G enerally,N i II -porphyrins tend to take non-planar structuress uch as ruffled and saddle-like conformationso wing to the relatively short NÀNi II distances, whereasZ n II -porphyrins prefer planars tructures. In addition,Li, Chmielewski, and co-workers also observed as imilare quilibrium in a pyrimidinenorcorrole dimer.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 4·PF 6 and 5·PF 6 show fluorescence at 578 nm (fluorescence quantum yield, Φ f = 2.6 % and fluorescence life time, τ f = 1.1 ns) and 616 nm (Φ f = 9.0 %, τ f = 2.3 ns), respectively. [51,52] In accord with previous research, we also considered the creation of the anti-aromatic boron complexes 6 and 7 from 4·PF 6 and 5·PF 6 . [36][37][38] In contrast, the highly planar and rigid structures of 4·PF 6 and 5·PF 6 with hydrogen bonding in the cavity induce higher fluorescence intensities, similarly to the thiophene-fused oxatriphyrins.…”
Section: Resultsmentioning
confidence: 84%
“…Ther adical was shown to be fairly planar with the two inner NH protons involved in the hydrogen-bond network. Norcorroles are [16]porphyrins-(1.0.1.0), and are remarkably stable,w hen suitably substituted, despite their strong antiaromatic characters.Aring expansion of norcorrole afforded the radical 36, [56] which existed in equilibrium with its C 2 -symmetric s-dimer with aC3 ÀC3' linkage.V ariable-temperature spectroscopic studies in toluene revealed the dissociation enthalpy to be 20.2 kcal mol À1 and the monomer content to be 12 and 90 %a t3 00 K and 373 K, respectively.The spectral changes were reversible under inert conditions.I np olar solvents,t his s-dimer underwent dehydrogenation to form the dimer 37,p robably by reaction with atmospheric oxygen. In 2018, Matanosg roup reported that 19p neutral radicals (38R)b ased on 5,10,20triaryl-5,15-diazaporphyrins were quite stable.…”
Section: Porphyrinoid-based and Other Macrocycle-based Radicalsmentioning
confidence: 99%